Археологія у науковому доробку Хведора Вовка, матеріали його досліджень у зібранні Національного музею історії України - Радієвська, Т.М. (Археологія і давня історія України, 2012)
Висвітлено археологічні дослідження у науковому доробку Хведора Вовка. Розглянуто колекції
матеріалів Мізинської палеолітичної стоянки,
дослідженої Хв. Вовком, що зберігаються в Національному музеї історії України. Археология занимала важное место в сфере научных интересов известного ученого и общественного
деятеля Федора Вовка. Во время политической эмиграции он познакомился с археологическими коллекциями музеев Вены, Праги, Цюриха. За время проживания в Париже Ф.K. Вовк прошел путь от студента
Сорбонны до известного ученого, и стал основоположником отечественной школы палеолитоведения, которая определила развитие первобытной археологии
на целое столетие. Всемирную известность ему принесла Мезинская стоянка, исследование которой проводилось на междисциплинарном уровне. Коллекция
материалов этого памятника хранится в Национальном музее истории Украины, и состоит из кремневых
изделий и шедевров искусства неоантропа. Также
объектом интересов исследователя было изучение трипольской культуры. Именно он познакомил европейский ученый мир с находками В.В. Хвойки. От популяризации раскопок Ф.К. Вовк пришел к теоретическим обобщениям об энеолитических культурах, внеся тем самым неоценимый вклад в науку. Archaeology played an important role in scientific
interests of the famous scientist and public figure Fedir
Vovk. Due to political emigration he’d got acquainted
with archaeological collections of museums in Vienna,
Prague, and Zurich. During his life in Paris F. Vovk
made the way from Sorbonne student to well-known
scientist. He also founded the domestic school of Paleolithic
study which determined the development of prehistoric
archaeology for the next century. He became
a world-known researcher after excavations in Mezin
site, explored by means of interdisciplinary approach.
Collection of artifacts from Mezin site is hold in the National
Museum of the History of Ukraine. It consists of
flint tools and masterpieces of late Paleolithic art. Besides,
Tripillian culture became the object of scientist’s
interest. Khvoika’s discoveries became well-known to
the European scientific world. After popularization of
archaeological excavations F. Vovk theoretically generalized
Eneolithic cultures, that made the inappreciable
contribution into Tripillian study.